Global Trade : Bad News, Good News - Rogerson, Evan (2018)
8 March saw two important events pulling the global trading system in opposite directions. On one side President Trump announced restrictive tariffs on steel and aluminium imports. On the other, 11 governments signed the CPTPP ̶ the TPP agreement without the US. What will be the outcome?